2018
DOI: 10.1177/0361198118790836
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pressure Aging Vessel Time to Field Aging of Binder as a Function of Pavement Depth and Time

Abstract: The AASHTO R28 pressure aging vessel (PAV) binder conditioning protocol has been heavily used for over two decades as part of purchasing specifications. Many paving industry changes have occurred since PAV was implemented in the early 1990s. This paper provides discussion with respect to a controlled test section in which the exact binders from construction were subjected to multiple PAV times and compared with properties observed after 2 or 4 years of field aging. The data suggests that 2 and 4 years of field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Mixture aging is complex and is more than binder oxidation (e.g., steric hardening, rearrangement), and aging is more than bond strength gains or losses and microcracking. Mixture aging is non-uniform (33,34), with oxygen and moisture diffusion occurring (35-37) alongside temperature gradients (6). These mechanisms also interact with the character of the mixture itself (e.g., void structure).…”
Section: Combined-effects Conditioning and Field Environmental Conditionsmentioning
confidence: 99%
“…Mixture aging is complex and is more than binder oxidation (e.g., steric hardening, rearrangement), and aging is more than bond strength gains or losses and microcracking. Mixture aging is non-uniform (33,34), with oxygen and moisture diffusion occurring (35-37) alongside temperature gradients (6). These mechanisms also interact with the character of the mixture itself (e.g., void structure).…”
Section: Combined-effects Conditioning and Field Environmental Conditionsmentioning
confidence: 99%
“…Performance-related binder specifications should therefore provide a means to select an appropriate binder in an economic, unbiased and competitive way, and should classify bituminous binders on unbiased grounds, while considering possible changes in the binder rheology experienced during the production and the service life of the asphalt layer (Smith et al 2018).…”
Section: Contact Detailsmentioning
confidence: 99%
“…Abdullah et al [20] added that the short-term ageing protocol (ASTM D2872 [6]) is not adequate for the simulation of asphalt's short-term ageing in tropical regions since high daily temperatures, humidity, and ultraviolet radiation significantly affect the physical and rheological properties of the asphalt. Smith et al [21] found that, through using samples extracted from a pavement surface layer aged 6.5 years, a PAV test protocol of 20 h simulated two years of ageing. For asphalts extracted from the top, in a depth of 1.3 cm, 21 h in the PAV represented two years of ageing in the field, and 45 h in the PAV represented four years of ageing in the field.…”
Section: Introductionmentioning
confidence: 99%